Health impaired employees' job satisfaction: New evidence from Athens, Greece - Nick Drydakis (Institute for the Study of Labor (IZA), 2011)
By utilizing the 2008 Athens Area Study (AAS) data set, this study investigates four aspects of job satisfaction - total pay, promotion prospects, respect received from one's supervisor, and total job satisfaction - between healthy and heath-impaired employees. Health impaired employees are found to be less satisfied according to all job satisfaction measures even when a large number of productivity features, and job characteristics are controlled for. The outcomes suggest also that women are more satisfied with their jobs than men are, regardless of health status. Moreover, the estimations show that health impaired employees' job satisfaction is affected more than healthy employees' job satisfaction by adverse mental health symptoms (life dissatisfaction). Finally, health impaired employees are found to become more satisfied with their jobs with time after disability onset. The study concludes that health impaired employees may have higher expectations about what they will obtain from their work, and that they may have job satisfaction adjustments.
urn:nbn:de:101:1-201107283751
Keywords: J10; J28; 330; health impairments; job satisfaction; ordered probit model; switching regression model; two-step quasi-likelihood exogeneity test